Adenylate cyclase influences filamentous haemagglutinin-mediated attachment of Bordetella pertussis to epithelial alveolar cells - Pérez Vidakovics, María Laura Anabella (2006)
Attachment to epithelial cells in the respiratory tract is a key event in Bordetella pertussis colonization. Filamentous haemagglutinin (FHA) is an important virulence factor mediating adhesion to host cells. In this study, the relevance of the interaction between FHA and adenylate cyclase toxin (ACT) during bacterial attachment was investigated. Mutants lacking either FHA or ACT showed significantly decreased adherence to epithelial respiratory cells. The use of several ACT-specific monoclonal antibodies and antiserum showed that the decrease in attachment of strains lacking ACT expression could not be explained by the adhesin-like activity of ACT, or a change of any of the biological activities of ACT. Immunoblot analysis showed that the lack of ACT expression did not interfere with FHA localization. An heparin-inhibitable carbohydrate-binding site is crucial in the process of FHA-mediated bacterial binding to epithelial cells. In the presence of heparin attachment of wild-type B. pertussis, but not of the isogenic ACT defective mutant, to epithelial cells was significantly decreased. These results suggest that ACT enhances the adhesive functions of FHA, and modifies the performance of the FHA heparin-inhibitable carbohydrate binding site. We propose that the presence of ACT in the outer membrane of B. pertussis to play a role in the functionality of FHA.